Complex factors shape phenotypic variation in deep-sea limpets. (31st October 2019) - Chen, Chong; Watanabe, Hiromi Kayama; Nagai, Yukiko; Toyofuku, Takashi; Xu, Ting; Sun, Jin; Qiu, Jian-Wen; Sasaki, Takenori
Abstract : Pectinodontid limpets are important members of deep-sea hot vents and cold seeps as can be seen by their conspicuous presence in both extant and extinct systems. They have traditionally been classified into different genera and species based on shell and radula characteristics; the reliability of these characters has been questioned but not tested thoroughly. Here, for the first time in taxa endemic to deep-sea chemosynthetic ecosystems, we combine substrate translocation with molecular data to assess the plasticity and variability of key phenotypic characters. Molecular data revealed that several 'species' of extant vent/seep pectinodontids actually represent intergrading morphotypes of a single, highly plastic, evolutionary lineage, with each morphological trait being possibly influenced differently by environmental and genetic factors. Our results challenge previous interpretations of paleoecology at fossil chemosynthetic ecosystems and highlight the importance of modern analogues in understanding fossil systems.